Evaluation of Rhodocyclus gelatinosus biomass for broiler pigmentation - Ponsano, E. H.G. [UNESP] (2002)
We evaluated the influence of dietary inclusion of corn gluten meal, apocarotenoic acid ethyl ester (APO-EE), canthaxanthin, and Rhodocyclus gelatinosus R1 biomass on broiler carcass color. These oxycarotenoid sources were used as pigment supplements to a basal ration containing yellow corn as the sole source of xanthophylls. Objective color values of L (lightness), C (chroma), and h (hue) were measured on skin and meat surfaces of broiler carcasses. On both surfaces, R. gelatinosus R1 biomass oxycarotenoids enhanced the chroma values (color saturation), as compared to yellow corn xanthophylls, and tended to provide yellowness to broiler carcasses, whereas the APO-EE and canthaxanthin tended to provide redness. At the concentrations studied, R. gelatinosus R1 biomass oxycarotenoids were less effective than APO-EE and canthaxanthin in enhancing color saturation. Lightness, chroma, and hue values did not differ significantly between males and females. However, skin showed significantly higher color saturation than meat in breast and thigh portions ofthe carcass. © 2002 Poultry Science Association, Inc.